Digital transformation and debt financing cost: A threefold risk perspective - Liu, Ethan Xin; Dang, Lily (Journal of Financial Stability, 2025)
This paper reports the results of an investigation of the impact of digital transformation on debt financing costs. By integrating information asymmetry theory and agency theory, we have developed a threefold risk-theoretic model to demonstrate how corporate digital transformation affects a firm’s debt financing costs. Drawing on a dataset of Chinese listed companies from 2007 to 2022, we measured digital transformation across three dimensions: attention, investment, and outcomes. The findings reveal that corporate digital transformation significantly reduces the cost of debt financing for companies. Mechanism tests indicate that digital transformation reduces debt financing costs by mitigating information risk, agency risk, and earnings risk through enhanced information disclosure quality, strengthened corporate governance, and improved expected earnings. Our paper not only enriches emerging research on the impact of corporate digital transformation on financial accounting but also provides theoretical insights for effectively alleviating the issue of expensive financing.